Animal care: an Islamic perspective with particular reference to unwanted pets- stray dogs and cats - Min, Myat; Zaw, Cho Cho (Zesdyzar Rokman Resources, 2016)
The topic of animal care especially the area of “unwanted pets in Islam” is rarely distributed among Muslim scholars, scientists and sociologists even though animal rights movement and animal activists are obviously increased among modern society. Small animals - dogs, and cats have been staying together with people since the beginning of human history. Humans have been receiving numerous benefits from them, such as keeping them as companions, using them for hunting, house keeping, and conducting research studies. The number of stray dogs and cats population on the streets has increased unexpectedly nowadays, and the risk of getting injury or disease from them becomes a huge concern for the community. Some people treated animals with cruelty, and there has been widespread abuse of them in the society. Animals are part of Allah (SWT) creations, and the Qur’an and the Al-Hadith prohibit cruelty to them and guides us to have mercy on them. As Muslims, Islamic teachings and concepts should be contemplated and incorporated in our daily activities. This study was conducted with the purpose of collecting authentic guidelines in Islam and exploring the view of Muslim scholars regarding animal care. The qualitative, library based approach was used as a research methodology and the data were exclusively sought from Holy Qur’an, Sunnah, books, journals, and Islamic manuscripts. The rights of animals, and human responsibility towards them were clearly presented from the perspectives of Islam. This study pointed out the need for maintaining balance between animal rights, and human benefits, focusing on treating animals with mercy, and reducing their sufferings even in times of killing them as a necessity. The study suggested that a need for developing a strategy by the relevant authorities regarding guidelines on some controversial issues such as animal neutering, spaying, and euthanasia to reduce the problems of pet owners, as well as to prevent the dangers of zoonotic diseases in the community. This study also serves as a comprehensive overview for the readers that assist them in obtaining knowledge, and increase their understanding of animal care in Islam. And it was expected to make a contribution to pet lovers in order to facilitate necessary prevention before their pets become unwanted and a burden to them.